2022
DOI: 10.3389/fbioe.2022.1019459
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of mesenchymal stem cell-derived exosomes in gastrointestinal cancers

Abstract: Gastrointestinal tumours are the most common solid tumours, with a poor prognosis and remain a major challenge in cancer treatment. Mesenchymal stem cells (MSC) are multipotent stromal cells with the potential to differentiate into multiple cell types. Several studies have shown that MSC-derived exosomes have become essential regulators of intercellular communication in a variety of physiological and pathological processes. Notably, MSC-derived exosomes support or inhibit tumour progression in different cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 203 publications
0
4
0
Order By: Relevance
“…Microvesicles (MVs), conversely, are formed by direct outward pinching or budding of the cell's plasma membrane, whereas apoptotic bodies are discharged into the extracellular space by dying cells [ 137 ]. Recent research has revealed that tumor-cell-derived exosomes play an important role in communication by transporting numerous biomolecules such as proteins, lipids, DNA, and RNA [ 138 ]. The cargo of exosomes closely resembles the intracellular components of their parent cells.…”
Section: Exosomes-based Therapies Targeting Stat3mentioning
confidence: 99%
“…Microvesicles (MVs), conversely, are formed by direct outward pinching or budding of the cell's plasma membrane, whereas apoptotic bodies are discharged into the extracellular space by dying cells [ 137 ]. Recent research has revealed that tumor-cell-derived exosomes play an important role in communication by transporting numerous biomolecules such as proteins, lipids, DNA, and RNA [ 138 ]. The cargo of exosomes closely resembles the intracellular components of their parent cells.…”
Section: Exosomes-based Therapies Targeting Stat3mentioning
confidence: 99%
“…A number of studies have pointed out the double-edged properties of MSC-EVs in the tumor environment, confirming that MSC-EVs play a dual role in promoting and inhibiting multiple stages of tumorigenesis ( Figure 3 ) [ 11 ]. Similarly, as for instance with cancer-cell-derived EVs, MSC-EVs have also been reported to play an important role in mediating tumor proliferation, angiogenesis, apoptosis, tumor invasion, dormancy, or resistance to chemotherapy/radiotherapy [ 126 ]. This inconsistency over the dual effect of MSC-EVs on tumorigenesis may be facilitated by many factors, including cell origin, experimental design, culture conditions, method of EV administration, or the tumor microenvironment (TME)–MSC-EV crosstalk.…”
Section: Distinct Roles Of Msc-evs In Cancer Biologymentioning
confidence: 99%
“…The exosomal hTERT-mRNA level is more elevated in Lynch syndrome mutation carriers (MSH2, MSH6), especially in metastatic colon cancer [ 77 ]. Exosomes, with the help of STAT pathways, could be a novel intermediate in the part of MSCs in GC promotion, and MSC-derived exosomes may be an unexplored therapeutic target not only for GC and ovarian cancer treatment but also for novel diagnostics of Lynch syndrome [ 46 , 76 , 78 , 79 , 80 ].…”
Section: Potential Therapeutic Implication Of Jak/stat Pathwaymentioning
confidence: 99%